PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATERI LUAS PERMUKAAN DAN VOLUME PRISMA DI KELAS VIII A SMP KRISTEN GPID PALU: Application Of Discovery Learning Model To Improve Students' Learning Achievements On The Material Of Surface Area And Volume Of Prisms In Class Viii A Of Gpid Christian Smp Palu - Dewi, Ni Gusti Ayu Kartia; Hasbi, Muh.; Murdiana, I Nyoman (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
The purpose of this research is to describe the application of discovery learning model to improve students' learning achievement in surface area material and prism volume in grade VIII A Kristen GPID junior high school, Palu. The type of research is class action research (PTK). The design of the research refers to the research design of Kemmis and Mc. Taggart which consists of four components, namely (1) planning; (2) action; (3) observation; and (4) reflection. This research conducted in two cycles. The subject of the study was a grade VIII student at GPID Palu, Christian Junior High School, with 16 students, consisting of 7 male students and 9 female students. The results of the study showed that the observation results of the activities of teachers in cycle I are obtaining the criteria of good success level, and have improved in cycle II, that is obtaining the criteria of excellent success level. The percentage of classical learning completion of cycle I is 67% and in cycle II is 81%. The results of this study showed that the application of discovery learning model can improve student learning achievement by following the phases of discovery learning model, namely: (1) stimulation or stimulation, in this phase the teacher gives problems about surface area and prism volume, (2) statement or problem identification (problem statement), in this phase the teacher asks students to hypothesize from the problem in the first phase, (3) data collection, in this phase the teacher invites students to collect information that used to solve problems, (4) data processing, in this phase the teacher asks students to fill out the LKS with their group friends and percentage in front of the class, (5) verification, in this phase the teacher asks students to do LKS 2 which is to prove the formula that has been obtained in a different way so as to obtain the same concept , and (6) draw conclusions and generalizations that are concluding the material studied.